Uptake of the Ithaka mobile application in Johannesburg, South Africa, for human immunodeficiency virus self-testing result reporting - Alex E. Fischer; Mothepane Phatsoane; Mohammed Majam; Luke Shankland; Musaed Abrahams; Naleni Rhagnath; Samanta T. Lalla-Edward (AOSIS, 2021)
Background: Human immunodeficiency virus self-testing (HIVST) can reduce facility-based HIV testing barriers; however, no proven applications exist with widespread uptake for self-reporting or linkage to care. Mobile health (mHealth) applications (apps) have shown high usability and feasibility scores, so Ithaka was developed for South Africans to self-report HIVST results outside clinical settings. Objectives: This study investigated the use of Ithaka as a support tool for HIVST users, specifically the ability to self-report results. Method: This cross-sectional study was conducted from November 2018 to June 2019. At existing HIVST distribution sites, individuals were given HIVST kits and then invited to use Ithaka. Participants could test at home and report their results through the app anytime. Ithaka tracked when people logged-on, registered, received counselling and reported results. Post-study surveys on user experience were also conducted. Results: Of 751 participants, 531 (70.7%) logged onto the app, 412 (54.9%) registered, 295 (39.3%) received counselling and 168 (22.4%) self-reported results. Participants strongly agreed that Ithaka was useful and that it was easy to upload results. Forty-one participants completed a post-test survey, and 39/41 (95.1%) completed the app journey. Most participants (36/41;87.8%) had no challenges, although 2/41 (4.9%) cited perceived data costs, 2/41 (4.9%) difficulty uploading results and 1/41 (2.4%) language, as challenges. Conclusion: Despite the small sample size, this study has shown that HIVST participants under pragmatic conditions were willing and able to self-report results via the app, whilst also identifying areas of improvement for scaling up.